EKSISTENSI BADAN PEMBINAAN IDEOLOGI PANCASILA (BPIP) DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA - Burhanuddin (Fakultas Hukum Universitas Gunung Rinjani, 2020)
Research to determine the position of the Pancasila IdeologyDevelopment Agency in the state administration system of theRepublic of Indonesia. This agency was formed as a concrete effortby the government to carry out its function as state administrator inresponding to the developing political situation in society, related tothe emergence of several political currents and identity politics whichare closely related to the role of Pancasila as the state ideology.Previously the President had issued Presidential Decree Number 54 of2017 concerning UKP-PIP which was considered to make it difficultfor the agency to coordinate with ministries and state agencies,because the UKP-PIP's authority was still at the level of the Ministry'sDirector General. This research uses normative legal research withstatutory and conceptual approaches. The analysis technique used isqualitative analysis by collecting legal material and then editing it firstto be used as material for analysis that is qualitative in nature.